Proceedings of the 1st International Conference on Education Social Sciences and Humanities (ICESSHum 2019) 2019
DOI: 10.2991/icesshum-19.2019.61
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Competitive Graduates of Vocational School through Revitalization Program

Abstract: The aim of vocational education is to prepare future generations who have high capability and competitiveness in facing the challenges of global labor competition in the 21st century and the 4.0 industrial revolution. This study aimed to find out: 1) profile of SMK Negeri 1 Buduran, 2) coverage of revitalization programs of SMK Negeri 1 Buduran, and 3) School Conditions of Before and After Revitalization. It was a qualitative descriptive study. The study was conducted in August-December 2017. The subjects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…To serve this purpose, learning processes at schools must give a high priority to direct practices in orde that they not only advance students' knowledge but also develop their professional competence. Nurlaela, et al (2019) stressed that revitalizing vocational education programs may strengthen partnerships of school with both industries and universities. The revitaliation program is also necessary for the curriculum uniformity among vocational schools.…”
Section: Resultsmentioning
confidence: 99%
“…To serve this purpose, learning processes at schools must give a high priority to direct practices in orde that they not only advance students' knowledge but also develop their professional competence. Nurlaela, et al (2019) stressed that revitalizing vocational education programs may strengthen partnerships of school with both industries and universities. The revitaliation program is also necessary for the curriculum uniformity among vocational schools.…”
Section: Resultsmentioning
confidence: 99%
“…By making a block schedule, a week for full vocational practicum, a week for general subjects, the problem is that we still have a lack of teachers, both vocational and general teachers. (PU4) Nurlaela et al (2019) mentioned that the key to the success of vocational revitalization is the collaboration between the industry, the vocational school, and universities. A teaching factory is a breakthrough where students can gain real learning experiences as much as possible during their studies.…”
Section: Still Pioneering Industry-based In Collaboration With Amaris Hotel a Learning Model With A Team Block System Curriculum (Practicmentioning
confidence: 99%
“…The study concluded that there are six contributions of the machinery industry in the revitalization program, namely: building link and match; apprenticeship program; a teacher internship program; industry-based class program; curriculum development; and teaching factory program. The results showed that the contribution level was very low, while Nurlaela et al (2019) mentioned that the key to the success of vocational revitalization is the collaboration between the industry, the vocational school, and universities. This is in line with the case study conducted by Muchtar (2019) in two vocational schools in Bandung.…”
Section: Introductionmentioning
confidence: 99%